Lev Vygotsky between two revolutions: on the political self-determination of the scientist - Vladimir S. Sobkin; Tatiana A. Klimova (Национальный психологический журнал, 2016)
The paper presented texts of the three previously unknown Lvygotsky’s journal notes and comments on them. These texts were published in mid-July and early September 1917 in the Jewish weekly «New Path» under the pseudonym «L.S.» and «W». In these texts, Lev Vygotsky describes the features of the political behaviour of the Jewish population in connection with the revolutionary events in Russia. On the one hand, a clear discrepancy between the activation of party work and political rhetoric is mentioned, and on the other hand, reduction of the significance of Jewish communal life is highlighted. As a key characteristic of social and psychological wellbeing of the Jewish population Vygotsky singles out absenteeism, i.e. the lack of interest in politics. Eventually the scientist captures the increase in uncertainty in the Jewish environment and fear of the future political, social and economic reforms in Russia. In the comments on Vygotsky notes, there are definitions relating to the various features of the activities of the Jewish political parties and public organizations, information about various policy documents and staff characterized by social and political situation before the elections in the Consituent Assembly (Uchreditel’noe Sobranie). Particular attention is paid to the analysis of stylistic and structural features of the commented text construction. By implicit quoting the relationship between Vygotsky’s texts and the works of other authors is identified. Particular attention is paid to the author’s attitude to religious texts, which allows to select a characteristic feature of the «double vision» of real events of the revolution against the background of the Jewish history. The comments help to single out features of the political identity of the young Lev Vygotsky in the period between the two revolutions, which is important to study his biography and understanding of his world view.